PENDEKATAN KOMUNIKATIF DALAM PEMBELAJARAN BAHASA ARAB - Mursidin M.Pd. (The Center for Language Development, Mataram State Islamic University., 2016)
Abstaract: Language as a tool, not as a goal’ becames the most basic principal of designing communicative approach in the learning of foreign language. In this way, teaching foreign language should make students not only have recep competence but also demonstrative one. The problem that mostly comes is merely related to how to design and handle such way in the real teaching. This paper just give san alternative perspective in applying a communic ative approach in learning Arabic.